The Role of Local Governments in Increasing the Human Development Index as a Barometer in Achieving SDGs in Boalemo District - Heldy Vanni Alam; Mahludin H. Baruwadi (Conference Series, 2020)
This study aims to: 1) determine the trend of the Human Development Index in Boalemo District and 2) describe the role of local governments in increasing the Human Development Index as a barometer in achieving SDGs. The research method used was a survey with secondary data obtained through various supporting documents available at the Statistics Indonesia and related Service Apparatus Organizations in time series and cross-sections. Data were then processed using descriptive analysis. The results showed that: 1) The Human Development Index in Boalemo District tends to increase from year to year and 2) Local government plays a vital role in developing human resources through education and health, which is implemented starting from the process of planning, organizing, implementing, to evaluating the program. Besides, the government's role is manifested in a commitment to support sustainable budgeting to increase the HDI SDGs optimally.